Synthesis and characterization of coal fly ash and palm oil fuel ash modified artisanal and small-scale gold mine (ASGM) tailings based geopolymer using sugar mill lime sludge as Ca-based activator - Einstine M. Opiso; Carlito B. Tabelin; Christian V. Maestre; John Paul J. Aseniero; Ilhwan Park; Mylah Villacorte-Tabelin (Heliyon, 2021)
The continuous accumulation of artisanal and small-scale gold mining (ASGM) tailings in the Philippines without adequate storage and disposal facility could lead to human health and environmental disasters in the long run. In this study, ASGM tailings was simultaneously stabilized and repurposed as construction material via geopolymerization using coal fly ash, palm oil fuel ash and a powder-based alkali activator. Scanning electron microscopy with energy dispersive X-ray spectroscopy (SEM-EDS) identified iron sulfides in the tailings containing arsenic (As), cadmium (Cd), copper (Cu), lead (Pb) and zinc (Zn), which could be released via weathering. The average unconfined compressive strengths (UCS) of tailings-based geopolymers at 14 days curing were 7.58 MPa and 7.7 MPa with fly ash and palm oil fuel ash, respectively. The tailings-based geopolymers with palm oil fuel ash had higher UCS most likely due to CASH reaction product formation that improved strength formation. The toxicity characteristic leaching procedure (TCLP) results showed very low leachabilities of As, Pb and Fe in the geopolymer materials suggesting ASGM tailings was effectively encapsulated within the geopolymer matrix. Overall, the geopolymerization of ASGM tailings is a viable and promising solution to simultaneously stabilize mining and industrial wastes and repurpose them into construction materials.